CHARACTERISTICS OF COGNITIVE LINGUISTICS - Eshonkulova Nasiba Khasanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article is devoted to the history of cognitive linguistics and who works in this area. Also, we may see several tasks of cognitive linguistics in this article.